A cross-sectional study on knowledge, attitude and practice regarding hypertension among the population age 18 years old and above in the area of sungai Kerubong, Sarikei from 6th July to 29th August 2008 - Audrey, Albert Radin; Azwan, bin Rahaman; Fatim, Zulaika; Henrietta, Albela; Shyang, Kho Sze; Hua, Lau Ee; Mohad Suhaimi, bin Sulaiman; Wen, Ngua Chen; Norain, binti Omar; Nur Aimi, binti Jaddil @ Zaidel; Nurul Aizam, bt Mohd Azmi; Siti Sanaa, binti Wan Azman; et al. (Universiti Malaysia Sarawak, (UNIMAS), 2008)
Hypertension is becoming an increasingly common health problem globally. In 2002, WHO estimated that there are a staggering 1 billion individuals with hypertension and 7.1 million deaths yearly contributed to hypertension. Currently, it is estimated that the number of hypertensive patients in Malaysia is 4.8 million, according to the Ministry of Health. It is even more disquieting that approximately two-thirds of individuals with hypertension in Malaysia were unaware that they were hypertensive.